2012
DOI: 10.1111/j.1442-9993.2012.02421.x
|View full text |Cite
|
Sign up to set email alerts
|

A survey of long‐term terrestrial ecology studies in Australia

Abstract: Long-term ecological studies (LTES) are critical for understanding and managing landscapes. To identify important research gaps, facilitate collaborations and communicate results, several countries have established long-term ecological research networks. A few initiatives to create such a network in Australia have been undertaken, but relatively few published data exist on the current state of LTES in Australia. In this paper, we present the results of an online survey of terrestrial LTES projects sent to acad… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 31 publications
0
5
0
Order By: Relevance
“…Youngentob et al . ). This is critical for taking ecological, financial and policy advantage of pre‐existing long‐term work with an already documented time series of information.…”
Section: Characteristics Of Effective Ecosystem Monitoring By 2050mentioning
confidence: 97%
See 2 more Smart Citations
“…Youngentob et al . ). This is critical for taking ecological, financial and policy advantage of pre‐existing long‐term work with an already documented time series of information.…”
Section: Characteristics Of Effective Ecosystem Monitoring By 2050mentioning
confidence: 97%
“…Ideally, in 2050, we should have a readily accessible archive that is founded on, and extends, work that has documented what studies have previously been done, what studies are still current, what was measured, and what is still being measured and how (see Youngentob et al . ). Recognize that curating critically important environmental datasets comes at a non‐trivial cost (Berman & Cerf ).…”
Section: Specific Design Featuresmentioning
confidence: 97%
See 1 more Smart Citation
“…There is a growing literature establishing LTERM as a research methodology that includes identifying critical success factors and providing guidance on design (e.g. Lindenmayer & Likens 2009, Lindenmayer et al 2012, 2014Youngentob et al 2013;Burns et al 2018). This literature provided the basis for establishing the research and monitoring associated with the MRI.…”
Section: Establishment Of the Larger Mri As A Long-term Research Programmentioning
confidence: 99%
“…Australia itself has few studies exceeding 10 or 20 years in duration. In a survey of Australian terrestrial ecology studies using seven years duration as the criterion for long-term, Youngentob et al (2013) identified 85 long-term study sites with a median age of 23 years. Some significant long-term studies were excluded from their survey, but it is unlikely that the number of long-term ecological studies in Australia exceeding 20 years duration is much greater than 50 or 60.…”
Section: Graham R Fultonmentioning
confidence: 99%